[P165] Analysis of dose deposition in lung lesions: A modified PTV for a robust optimization. (August 2018) - Monti, Angelo Filippo; Brito, David Antonio; Brambilla, Maria Grazia; Carbonini, Claudia; Ferrari, Maria Bernadetta; Zanni, Daniela; Mainardi, Hae Song; Torresin, Alberto
Abstract : Purpose: SBRT in lung cancer delivers high doses to a small dense nodule (GTV) moving into a low density tissue. If an IMRT-VMAT technique is used, an apparently homogeneous dose is delivered, but an high photon fluence is generated inside the PTV-GTV shell due to its low electron density (ED). This gives the paradox that the dose distribution seems uniform, but the GTV, which moves into the PTV, will receive a dose depending on its position. Methods: A TPS "Monaco" (MC algorithm) was used to simulate a dummy patient (55 Gy in 5 fractions). In step 1, in order to evaluate the dose discrepancy on the target when the motion of the GTV is considered, the photon fluence was optimized for the original PTV ED (EDo) and thus used to calculate the dose on a "forced" PTV ED (EDf), in which the ED of the PTV was forced to the mean ED of the GTV. In step 2, the photon fluence was optimized for PTV EDf and then used for dose calculation on PTV EDo to evaluate the dose variation on the lower ED region of the PTV and inside the GTV. Dosimetric comparisons between the original and the recalculated dose distribution for PTV-GTV were made in terms of: dose profiles, Dmean, D98% and D2%. Results: In step 1 dose profiles differ up to 6.6%, 3.4% and 3.8% on longitudinal, sagittal and transversal axes along the isocenter. Increments of 1.6% for D98%, 2.5% for Dmean and 5% for D2% were obtained for PTV-GTV. In step 2 differences between dose profiles were −3% for all. A reductions of −1.5% for D98%, −1.5% for Dmean and −1.4% for D2% were achieved for PTV-GTV. Conclusions: Step 1 shows that the dose delivered to GTV, when it moves where the photon fluence is optimized for lower ED, is higher than what estimated on the original EDo. The GTV is irradiated in a more homogeneous way in step 2 in which the fluence is optimized for EDf. We propose to modify the PTV electron density thus considering the GTV mobility, and evaluating more effectively the actual GTV dose.